Structural and optical characterizations of thermal luminescence materials LiF:Mg,Cu,P and LiF:Mn,Co,P nanoparticles - Najeeb Al-Gburi, Farooq Abdulkhaleq (2017)
Varieties of materials have been used in the thermo luminescence dosimeters (TLDS). The physical and chemical properties of these materials have shown great enhancement especially in environmental, medical and industrial applications. Thermoluminescence materials have been synthesised using different methods which include solid state, gaseous phase, hydrothermal, combustion and sol gel methods. However, the application of most of these methods on large-scale production is difficult due to the complex nature of their procedures, toxic reagents, and longer reaction time, difficult to achieve high purity, and toxic by-products, which can harm the environment. In this research, the TLDS was fabricated using lithium fluoride (LiF) doped with Mg/Mn, Cu/Co, which is the tissue equivalency of this material (Zeff=8.04) suitable for use in personal dosimetry. Firstly, LiF:Mg,Cu,P and LiF:Mn,Co,P nanoparticles were synthesized separately using a modified co-precipitation and thermal treatment methods. In TGA, the weight of low molecular compounds is reduced at temperature ranging between 150 °C and 250 °C. Next, the factors of thermal stability including initial decomposition temperature (Tonset) are between 200 °C and 500 °C. Conversely, 470 °C (Tmax) is the required temperature for major weight loss of up to 86.67% due to PVP as capping agent. The formations of LiF nanoparticles were confirmed using FT-IR analysis showing two principle absorption bands at 370 and 850 cm-1 which can be attributed to Li-O and F-O, respectively. The XRD patterns of the LiF nanoparticles which have been synthesized indicated the peak positions at 2θ values of 38.797°, 45.104°, 65.691°, 78.988°and 83.254° corresponding with (111), (002), (022), (113) and (222) crystalline plans, which indicate cubical lithium fluoride nanoparticles. The calculation of the average crystallite size of all samples was done using the Scherer’s formula and this corresponded with the TEM images that possessing homogenous particle size distributions and morphology. It was observed that an increase in calcination temperature the average particle size increased from 1.66 nm at 450 °C to 3.34 nm at 750 °C. The UV-vis reflectance with the increase in the calcination temperature. The energy gap was calculated to be 4.28 eV at 450 °C to 4.20 eV at 750 °C for LiF:Mg,Cu,P nanoparticles while the energy band gap of LiF:Mn,Co,P nanoparticles reduced from 4.28 eV at 450 °C to 4.21 eV at 750 °C as a result of an increase in particle size.